Mechanical Properties and Microstructure Evolution Of AA6082/Sic Nanocomposite Processed by Multi-Pass FSP - Hashmi, Abdul Wahab; Mehdi, Husain; Mishra, R. S.; Mohapatra, Prabhujit; Kant, Neeraj; Kumar, Ravi (Transactions of the Indian Institute of Metals, 2022)
In this investigation, homogenously disseminated SiC reinforcement particles and a fine-grained structure was accomplished by multi-pass friction stir processing (MPFSP) of AA6082. The results revealed that refined grain structures with predominant high-angle grain boundaries were made in the stir zone in the 5th pass FSP due to severe plastic deformation and dynamic recrystallization. The MPFSP observed material flow around the cluster’s redistribution. At increased SiC concentration, the microstructure and electron backscatter diffraction (EBSD) examinations demonstrated that SiC reinforcement particles strongly inhibited grain boundary migration, resulting in an incessant decrease in grain size. The tensile properties and microstructure of the MPFSP/SiC were enhanced by employing a rotational tool speed (RTS) of 1450 rev/min, welding speed (WS) of 85 mm-min-1 with a tilt angle of 2°. The reinforcement particles were homogenously disseminated in the 5P FSP. The base metal AA6082's tensile strength was 219 ± 5 MPa with a % strain of 24.8 ± 0.3. After MPFSP/SiC on AA6082, the tensile strength was increased as the FSP pass increased. The higher tensile strength (298 ± 8 MPa) was observed at the 5P FSP, caused by fine grains during the dynamic recrystallization mechanism.